2013
DOI: 10.1007/s13762-013-0373-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving microbial oil production with standard and native oleaginous yeasts by using Taguchi design

Abstract: Production of microbial oil has attracted a great attention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
5
12
1
Order By: Relevance
“…In addition, fluorescence emission observed in Fig. was similar to those described in several oleaginous yeasts .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, fluorescence emission observed in Fig. was similar to those described in several oleaginous yeasts .…”
Section: Discussionsupporting
confidence: 84%
“…The high oleic and linoleic acids content observed here, and common for yeasts, is considered favorable for biodiesel applications . Furthermore, it has been concluded that yeast oils would be appropriate for use as biodiesel at a similar blending ratio as biodiesel originating from vegetable oils .…”
Section: Discussionmentioning
confidence: 64%
“…The pH was measured by a laboratory pH meter (METTLER TOLEDO FiveEasy, Switzerland). The concentration of glucose was determined by the 3,5-dinitrosalicylic acid (DNS) method [44,45]. NH 4 + concentration was measured by the indophenol blue spectrophotometric method [46].…”
Section: Determination Of Dry Cell Weight Ph and Glucose And Nitrogementioning
confidence: 99%
“…Glucose has been reported as the best substrate for microbial oil production, since it can be assimilated by most oleaginous microorganisms to produce oil [ 18 ]. Therefore, equivalent glucose contents from each collected waste were determined as described by Saeman et al [ 10 ] and Miller [ 11 ].…”
Section: Resultsmentioning
confidence: 99%